Eating behaviour, body image, and self-esteem of adolescent girls in Malaysia - Soo, Kah Leng; Mohd Shariff, Zalilah; Mohd Taib, Mohd Nasir; Abu Samah, Bahaman (SAGE Publications, 2008)
This cross-sectional study was undertaken with 489 secondary school girls, ages 15–17 years, to examine disordered eating behaviours of adolescent girls in Malaysia and to estimate associations with body weight, body-size discrepancy, and self-esteem. Dietary restraint, binge eating, body image, and self-esteem were assessed using the Restrained Eating scale of the Dutch Eating Behaviour Questionnaire, the Binge Scale Questionnaire, the Contour Drawing Rating Scale, and the Rosenberg Self-Esteem Scale, respectively. Pearson correlations estimated associations between variables. There were 3.1% underweight, 9.8% at risk of being overweight, and 8.6% overweight girls. A total of 87.3% were dissatisfied with their own body size. Dietary restraint and binge eating were reported by 36.0% and 35.4%, respectively. Body Mass Index (r = .34, p < .01) and body-size dissatisfaction (r = .24, p < .01) were significantly associated with dietary restraint and binge eating, but self-esteem (r = −.20, p < .001) was significantly associated only with binge eating.